A turnkey gaseous helium-cooled superconducting CORC® dc power cable with integrated current leads. (1st June 2022) - van der Laan, D C; Kim, C H; Pamidi, S V; Weiss, J D
Abstract: High-temperature superconducting (HTS) direct current (dc) power cable systems, capable of delivering power exceeding 10 MW while being cooled with cryogenic helium gas, have been developed for applications on naval electric ships, electric aircraft and in data centers. Current injection from room temperature into the superconducting power cable causes by far the greatest heat load to the cryogenic system. Efficient current leads with integrated helium gas heat exchangers were developed to inject a current exceeding 1 kA from room temperature into a superconducting Conductor on Round Core (CORC ® ) power cable, without the need for liquid nitrogen pre-cooling. A 2 m long single-pole CORC ® power cable system that included current leads was cooled using a Stirling cryocooler with a closed-loop helium gas circulation system. The turnkey power cable system allowed cool down from room temperature to its operating temperature of 60 K–70 K within 5 h, after which continuous operation at 1.2 kA was demonstrated. The successful development and demonstration of a CORC ® power cable with current leads containing integrated helium gas heat exchangers enables widespread implementation of HTS MW-class, high current density superconducting dc power cables in many applications with constrained space that require a power dense solution.